Landbird Richness and Abundance in Three Coastal Habitats Near Resorts in Cayo Coco, Cuba - Wiancko, Erin; Nol, Erica; Parada, Alain; Burke, Dawn M (The Condor (Los Angeles, Calif.), 2011)
We studied habitat use of disturbed coastal forest by communities of North American migrant and Cuban resident land birds on Cayo Coco, Cuba. This region is subject to a growing resort industry, yet the ecological effects of this disturbance remain largely unknown. Using mist-nets, we sampled birds during two early winters and one late winter. We sampled at sites adjacent to coastal resorts, and at a distance of up to 5.7 km from resorts, in three habitat types (mixed mangrove, semi-deciduous, and coastal scrub forests). We tested for differences in abundance and richness at sites near and far from resorts and among the three habitat types. We also assessed whether bird distribution was associated with fruit abundance and/or vegetation characteristics. Across seasons, migrants were consistently more abundant at sites near resorts than at sites more distant, whereas richness of Cuban residents was consistently higher at sites near resorts than at those farther away. Neither abundance nor richness of the resident guild varied significantly by habitat. The distributions of neither migrants nor residents were correlated with fruit abundance. High foliage density associated with greater edge habitat provided the strongest explanation for high estimates of abundance and richness of migrants and residents near resorts. Our results suggest that moderately disturbed forests near resorts can support abundant and rich communities of both migrants and residents. [PUBLICATION ABSTRACT]